2021
DOI: 10.3390/app11198791
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Ankle Fractures in Plain Radiographs Using Deep Learning with Accurately Labeled Datasets Aided by Computed Tomography: A Retrospective Observational Study

Abstract: Ankle fractures are common and, compared to other injuries, tend to be overlooked in the emergency department. We aim to develop a deep learning algorithm that can detect not only definite fractures but also obscure fractures. We collected the data of 1226 patients with suspected ankle fractures and performed both X-rays and CT scans. With anteroposterior (AP) and lateral ankle X-rays of 1040 patients with fractures and 186 normal patients, we developed a deep learning model. The training, validation, and test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In this study, we introduced a dataset of annotated ankle x-rays and demonstrated the effect of its multiclass labeling by performing network training on the task of automated fracture detection on distinct subsets of images, thus quantifying the influence of selected image features. By utilizing customized state-of-the-art preprocessing and augmentation methods on both the images themselves as well as the composition of the training data set, our study performed better compared to most contemporary ankle studies, including both convolutional neural networks [ 16 , 17 ] and traditional machine learning methods [ 18 ]. For convolutional neural networks, the prevalent training protocol incorporates random dataset augmentation as performed in our study as well as triplication of the medical image for use on imagenet-pretrained networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we introduced a dataset of annotated ankle x-rays and demonstrated the effect of its multiclass labeling by performing network training on the task of automated fracture detection on distinct subsets of images, thus quantifying the influence of selected image features. By utilizing customized state-of-the-art preprocessing and augmentation methods on both the images themselves as well as the composition of the training data set, our study performed better compared to most contemporary ankle studies, including both convolutional neural networks [ 16 , 17 ] and traditional machine learning methods [ 18 ]. For convolutional neural networks, the prevalent training protocol incorporates random dataset augmentation as performed in our study as well as triplication of the medical image for use on imagenet-pretrained networks.…”
Section: Discussionmentioning
confidence: 99%
“…Kim and colleagues achieved a mean AUC of 0.89 on ap-views using the pretrained Inceptionv3-network architecture without layer customization on a similarly sized dataset of 1226 examinations and a comparable augmentation scheme [ 16 ]. The ratio of positive to negative images was almost inverted with mostly fractured ankles (85% against 15%), which for a binary classification task should result in a comparable sampling bias.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding previous DL models for diagnosing ankle pathologies using ankle radiographs as input data, only models for diagnosing ankle fractures have been developed. [19][20][21] The accuracies were reported to be approximately 80% to 90%. To the best of our knowledge, this study is the first to demonstrate the possibility of diagnosing OLTs using DL algorithms trained using ankle radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…In light of recent advancements in deep learning for ankle fracture detection, studies [ 21 ] and [ 22 ] have demonstrated the efficacy of employing deep convolutional neural networks (DCNNs) with radiographic images. Study [ 21 ] reported a high sensitivity of 98.7% and specificity of 98.6% using Inception V3 and ResNet-50 on radiographs, emphasizing the potential of DCNNs to accurately identify fractures from multiple views.…”
Section: Introductionmentioning
confidence: 99%